Smart Marriage Contracts: The Future of Blockchain in Matrimonial Property Law? (Zbornik Pravnog fakulteta Sveučilišta u Rijeci, 2022)
This paper is intended to serve as an introductory treatise on the subject of smart marriage contracts (SMC) as a manifestation of blockchain in matrimonial property law of contracts. We start with a description of the origin and functioning of a SMC from a technical standpoint, while evaluating the legal nature thereof at the same time. Afterwards, we focus on the possibilities and means of a SMC’s establishment under German, Austrian, and Slovak law. Moving on, issues related to the content of a marriage contract establishing a SMC are examined. We then test the permissibility of a SMC-related provision in a marriage contract referred to as a “registration clause”.The key findings of our research run as follows. SMC’s can be established via marriage contract under German and Austrian law, yet they cannot be established under Slovak law. Regarding the proper content of a marriage contract establishing a SMC, there are several factors to which drafters should pay close attention in order to ensure the desired functionality of a SMC. A registration clause in a marriage contract is invalid both under German and Austrian law due to the violation of good morals. The question of possible partial avoidance of a registration clause pursuant to BGB depends on the circumstances of an individual case; ABGB on the other hand allows partial avoidance of such a clause in every case.